Elaboración y aplicación de un manual de estimulación en la expresión oral y escrita para mejorar el proceso de lecto – escritura en los niños y niñas del primer año de educación básica paralelo “c” de la escuela Juan Pío Montúfar Juan de Dios Morales de la parroquia Mulaló cantón Latacunga provincia Cotopaxi en el año lectivo 2013 – 2014 - Bombón Benítez, Carmen Elizabeth (2014)
The present research has important aspects for improving reading and writing process on children of first year of basic education parallel “C” from the Juan Pío Montúfar Juan de Dios Morales school from Mulaló, Latacunga on Cotopaxi province by oral and writting stimulation. The research was developed when the problem was detected on the children. With this aport the goals of this job are presented in a clear way. These goals are based with teorics and practices on the elaboration of materials and fashion workshops. Also they`re interesting for children in order to get their attention….